2020
DOI: 10.1111/jai.14016
|View full text |Cite
|
Sign up to set email alerts
|

Length‐weight relationships of seven cyprinid fish species from the Kaptai Lake, Bangladesh

Abstract: Summary Length‐weight relationships (LWRs) were estimated for seven small indigenous cyprinid fish species including Securicula gora, Osteobrama cotio, Esomus lineatus, Pethia gelius, Megarasbora elonga, Gonialosa manmina and Glossogobius aureus occurring in the Kaptai Lake, Bangladesh. Fish were collected monthly basis between March and October, 2018 from fishermen catches landed in the fish landing center, Rangamati. Fishermen operated lift net (mesh size < 0.5 cm), punti net (mesh size < 0.5 cm) and cast ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
4
7
0
Order By: Relevance
“…However, in the present study, b > 3, indicated positive allometric pattern of growth in Catla catla that means large fish samples have grown more in weight than in length and robustness of large-sized specimens; or large samples were in good nutritional environments at sampling time (Froese, 2006). The results of the present study are in agreement with the study of Singh and Lakhwinder (2015), who have also reported b-value 3.20 for C. catla, and with the results of Hanif et al (2020) who have documented this value 3.21 in a cyprinid fish species (Glossogobius aureus) indicating positive allometric growth pattern. On the other hand, Kartha and Rao (1990) and Ishtiaq and Naeem (2016) have documented isometric growth in C. catla, representing large samples have the same condition and shape as small samples.…”
Section: Resultssupporting
confidence: 92%
“…However, in the present study, b > 3, indicated positive allometric pattern of growth in Catla catla that means large fish samples have grown more in weight than in length and robustness of large-sized specimens; or large samples were in good nutritional environments at sampling time (Froese, 2006). The results of the present study are in agreement with the study of Singh and Lakhwinder (2015), who have also reported b-value 3.20 for C. catla, and with the results of Hanif et al (2020) who have documented this value 3.21 in a cyprinid fish species (Glossogobius aureus) indicating positive allometric growth pattern. On the other hand, Kartha and Rao (1990) and Ishtiaq and Naeem (2016) have documented isometric growth in C. catla, representing large samples have the same condition and shape as small samples.…”
Section: Resultssupporting
confidence: 92%
“…For all species, the estimated b values were within the normal range of 2.5 to 3.5, as suggested by Froese (2006). Variations in the b values are usually attributed to several factors such as sample size, habitat, season, sex, diet, and gonadal maturity (Bagenal and Tesch 1978;Froese 2006;Hanif et al 2020). The size range covered for some species was narrow.…”
Section: Resultssupporting
confidence: 55%
“…Many authors reported ‘b’ values and correlation coefficients ( r 2 ) for different sister species of Schistura which are very closed to our present findings (Akhtar & Khan, 2018; Ansumal & Subba, 2009; Froese & Pauly, 2019; Keskar et al, 2015; Negi, 2013; Talukdar et al, 2017). Correlation coefficients ( r 2 ) value of the present study (between 0.9 and 1.0) indicated ideal growth of all species (Hanif et al., 2020). Different factors including a number of specimens, seasonality, diet, habitat, gear selectivity, sex ratio, size of fish, the fullness of stomach, growth stages, health and environmental conditions can influence the LWRs parameters (Froese, 2006; Siddik et al, 2016; Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 57%
“…Length‐weight relationships (LWRs) are basic biological parameters in fisheries science, assisting in assessing growth status of fish, age structure, regional comparison of fish life history, species‐specific approximate production and environmental suitability (Hanif et al., 2020). The length data can often be used to determine the biomass when only length data is available.…”
Section: Introductionmentioning
confidence: 99%